FISHING GEAR PERFORMANCE ON SKIPJACK TUNA IN BONE BAY DISTRICT LUWU - Akamlauddin Akmaluddin; Najamuddin Najamuddin; Musbir Musbir (OCTOPUS : JURNAL ILMU PERIKANAN, 2015)
Mayority fishing gear by Skipjack tuna as a main target by fisherman Distrit Luwu are using for operation di Bone Bay every year, so there is over eksploitation matter in some spesies of fish especially skipjack tuna as a main target. The Goal of study is to analysis of performance skipjack tuna fishing gear (pole and line, hand line, and payang) based on four aspect are biology, technical, social,and economi. Design of study is direct observation in the field using interview methode to choice responden as line owner of fihsing boat each skipjack fishing gear. Analysis use skoring methode with formula by Mangkusubroto and Trisnadi (1985). Result of study is the pole and line is the best in the technical aspect and economi aspect, but hand lineis  the best in biology aspect and social aspect. The main priority fishing gear in succession is first pole and line, second hand line and last payang. The conclution is the fishing gear of pole and line have the best performance than others in District Luwu, beside that it’s suitable to be continued and developed in the future because it’s very adventageous and brief in payback periode.